2005
DOI: 10.1021/jf047892x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Ethylene Biosynthesis to Volatile Production, Related Enzymes, and Precursor Availability in Apple Peel and Flesh Tissues

Abstract: Regulation of ethylene biosynthesis or action has a major effect on volatiles production in apples. To understand the biochemical processes involved, we used Greensleeves apples from a transgenic line with a high suppression of ethylene biosynthesis. The study was focused at the level of the aroma volatile-related enzymes, including alcohol acyltransferase (AAT), alcohol dehydrogenase (ADH), and lipoxygenase (LOX) and at the level of amino acids and fatty acids as aroma volatile precursors in peel and flesh ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
117
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(139 citation statements)
references
References 37 publications
20
117
1
1
Order By: Relevance
“…The most important amino acids for the biosynthesis of volatile compounds in apples are GD (14) GS (14) MG (53) G R ( 45) FJ ( (76,77). The concentration of most amino acids decreases with the maturation of apples (78)(79)(80)(81) due to the synthesis and metabolism of proteins (78). During storage, an initial reduction in the content of amino acids occurs, without signifi cant change aft erwards (78).…”
Section: Biosynthesis Of Volatile Compounds In Applesmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important amino acids for the biosynthesis of volatile compounds in apples are GD (14) GS (14) MG (53) G R ( 45) FJ ( (76,77). The concentration of most amino acids decreases with the maturation of apples (78)(79)(80)(81) due to the synthesis and metabolism of proteins (78). During storage, an initial reduction in the content of amino acids occurs, without signifi cant change aft erwards (78).…”
Section: Biosynthesis Of Volatile Compounds In Applesmentioning
confidence: 99%
“…Fig. 2 shows the formation of volatile aroma compounds from linoleic and linolenic acids through the LOX pathway, and Table 3 shows some studies that have been performed on enzymes from the LOX pathway in diff erent developmental stages of apples (13,15,34,40,44,45,54,72,73,75,79,85,96,106,(118)(119)(120)(121)(122)(123)(124)(125)(126)(127)(128)(129)(130)(131)(132)(133)(134)(135)(136).…”
Section: Lipoxygenase Pathwaymentioning
confidence: 99%
“…Branched-chain esters are characteristic of many cultivars of apple, including Royal Gala (Young et al, 1996(Young et al, , 2004. These are produced from Ile (Rowan et al, 1996), which increases in quantity in apple fruit skin during ripening (Defilippi et al, 2005a). Ile is synthesized from the amino acid Thr via five enzymatic steps.…”
Section: Flavor Biosynthesismentioning
confidence: 99%
“…These observations agree with the well-known phenomena that apple ripening and aroma synthesis are promoted by ethylene. 21,22) Stronger correlations with flavor components than with QDA further indicated that flavor profiles were directly regulated by ethylene, and sensory descriptions varied accordingly. The present data demonstrate the utility of metabolite profiling for sensory descriptions of agricultural products.…”
Section: Discussionmentioning
confidence: 99%